Energy efficient Robust On-Demand Multicast Routing Protocol for MANETs. (5th February 2008) - Manoharan, R.; Thambidurai, P.; Lakshmana Pandian, S.
In Mobile Ad hoc Networks (MANETs), multicast routing protocols are being faced the challenge of producing multi-hop routes under severe resource constraints such as battery power, limited bandwidth and dynamic network topology. Multicasting in MANETs is complex and the overall energy is to be conserved as much as possible while achieving good throughput. In this paper, an energy efficient Robust On-Demand Multicast Routing Protocol (ROMRP) has been proposed to increase the overall throughput and the lifetime of multicast session by efficiently monitoring the group leader in order to preserve the multicast session without affecting loss of data packets and network partitioning.